City logistics : network modelling and intelligent transport systems - Taniguchi, Eiichi (Pergamon, 2001)
"The focus of this work is on modelling City Logistics. Modelling is of crucial importance, since estimates of the impacts by City Logistics measures are required for evaluating them. It highlights the formulation of mathematical models of vehicle routing and scheduling with Intelligent Transport Systems (ITS), optimal terminal locations and impact estimation by City Logistics measures. Heuristics techniques such as genetic algorithms simulated annealing and tabu search are also given to identify approximate optimal solution of these combinatorial optimisation problems."